Digital-Based Innovation in Qur’anic Learning at Taman Pendidikan Al-Qur’an: An Exploratory Sequential Design - Riadi, Ahsan; Al-Madani, Khalid; Anshori, Irfan; Anwari, Moh.; Atayev, Murat (STAI Publisistik Thawalib Jakarta, 2026)
Taman Pendidikan Al-Qur’an (TPQ) in pesantren environments has impeded advancements in Qur’anic education, specifically concerning the accommodation of student requirements and technological constraints. This study investigates the use of technology in digital TPQ instruction, aiming to identify challenges and suggest solutions to improve learning outcomes, student participation, and long-term success. The study used an Exploratory Sequential Design, starting with a qualitative case study that included interviews, observations, and document analysis. The qualitative findings then informed a quantitative descriptive phase, where a Likert-scale questionnaire was given to 30 respondents, and the data were analyzed using SPSS and Microsoft Excel. The survey results show that a significant 80.7% of the participants believe that digital innovation in TPQ successfully connects Qur’anic education with current developments. Teaching tajwid incorporates tools like laptops, projectors, audiovisual aids, and mobile applications. These resources are used to increase student motivation and encourage active participation. WhatsApp serves as a communication tool for teachers and parents, helping to monitor academic progress and encouraging teamwork. Moreover, a significant 78.4% of those surveyed highlighted the importance of carefully managing digital media use. In essence, digital innovation serves to augment motivation, foster engagement, and improve instructional efficacy, all while upholding the core principles of pesantren. This study contributes to the ongoing discussion regarding the incorporation of digital technology in TPQ environments, demonstrating its potential to improve educational results and develop Qur’anic teaching methodologies tailored to the particular context.